Web-Based Geographical Information System Mapping High School and Vocational School In The City Of Ternate - M. Ilham Maulana; Muhammad sabri Ahmad; Arifandi Mario M; Achmad Fuad (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The government of the Education Office of North Maluku Province is trying to overcome the problem of student distribution for schools in the city of Ternate, especially SMA/SMK/equivalent which aims to make all schools quality and there are no more superior schools. However, new problems arise related to the zoning system itself, sometimes some parents of prospective students and prospective students themselves do not know the schools in their domicile zone. The problem formulation is how to create and compile a Geographic Information System Mapping SMA and SMK in Ternate City. Designing a geographic information system that can provide information about web-based SMA and SMK Mapping in Ternate City and become a reference for the community in choosing their or their children’s schools according to the zoning system. For testing the system is in accordance with the stages tested where for testing the system is used black box testing, namely testing to see the suitability of data accessed. The high school and vocational recession geographic information system was built using the PHP programming language, Mysql as a database, while for making locations of high school and vocational high school vulnerable places using google maps, maps API. All high school and vocational tracking information system uploads use black boxes, run as expected on the system upload carried out. From the results of this design, it will make it easier for parents to find information on SMA and SMK schools, such as the domicile zone of the school where they live.